"Spirit to Spirit": The Imagery of the Kiss in the Zohar and its Possible Sources - Werthmann, Tanja (Harvard theological review, 2018)
The study explores the character and meaning of the imagery of the kiss in the Zohar as an expression of dynamic union. In order to demonstrate the formation of a specific structure of ideas and their dynamics within Kabbalistic theosophy, the Zoharic imagery found in the pericope Terumah has been situated here within the context of numerous sources, from which the Zohar, through direct or indirect transmission, could have drawn its key elements. The metaphor of the kiss, which allows the Zoharic homily to embrace several central Kabbalistic concepts of love, presents love as a universal power, being comprised of two Neoplatonic notions, the hypostatic relation and the principle of "being contained in each other." The analysis of the various sources across ancient Greek, medieval Islamic, and Christian traditions amounts to a different characterization of the meaning adduced thus far in scholarship regarding eros in Jewish mysticism and suggests a more plausible trajectory of influence of Greek sources in the early Kabbalah.